Phenylpyrimidine-Based Iridium Complex for High-Performance Green-Yellow Phosphorescent Organic Light-Emitting Diodes. Issue 1 (1st January 2022) - Bi, Y; Zhang, X Y; Li, H; Wang, T
Abstract: In this work, a phenylpyrimidine-based green-yellow iridium complex, (bpp)2 Ir(acac), is prepared. Tert-butyl group is introduced to weaken the intermolecular interaction and endow (bpp)2 Ir(acac) with favorable physical properties. Phosphorescent device which utilizes (bpp)2 Ir(acac) as the luminescent guest material displays high efficiencies (73.9 cd/A, 84.8 lm/W, 21.2%), low efficiency roll-off (from 100 to 10000 cd/m 2 : 5.1%), relatively low concentration sensitivity (from 5% to 12%) and very stable electroluminescent spectra (from 1 cd/m 2 to maximum luminance). As a consequence of the results proved that (bpp)2 Ir(acac) is a good phosphorescent material.